Penerapan Family Psychoeducation Online dalam Mengurangi Anxietas pada Klien Terkonfirmasi Covid-19: Case Report - Eli Saripah; Novy Helena Catharina Daulima; Herni Susanti; Ice Yulia Wardani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Backround: Covid-19 patients are prone to experiencing psychological disorders in the form of anxiety and fear. This psychological consequence strikes because the patient has excessive anxiety, especially physical conditions and limited interaction patterns in order to suppress the spread of the Covid-19 virus. Objective: The application of Family Psychoeducation to families based on standard mental nursing care is carried out online for clients to reduce anxiety levels in families who have family members with Covid-19. Methods: This case report uses the application of Family Psychoeducation and nursing care standards for Covid-19 clients who experience anxiety. This case report is based on the experience of clinical practice specializing in 2000 souls which was carried out online during the Covid-19 pandemic. Results: Evaluation has found a decrease in the level of anxiety in clients and families who are confirmed positive for Covid-19 which is done online. The therapist has also given pre and post test SRQ questionnaires where the client's score opens 8 and the SRQ opens 10. In this important case the intervention is carried out in order to reduce anxiety that occurs in the client and family. After the treatment process, the results of the client and family SRQ scores are 6 which means there is a decrease in the stress felt by the client and family during the client's treatment in the hospital. Conclusion: The application of Family Psycoeducation to families based on the standard of mental nursing care is carried out online for clients and families to reduce the level of anxiety in families whose family members have Covid-19 confirmed. The evaluation found that there was a decrease in anxiety levels in clients and families who were confirmed positive for Covid-19 which was carried out online.Keywords: anxiety; covid-19; family psychoeducationABSTRAKLatar belakang: Pasien covid-19 rentan mengalami gangguan psikologis berupa kecemasan dan ketakutan. Konsekuensi psikologis ini menyerang karena pasien memiliki kecemasan berlebih terutama kondisi fisik dan pola interaksi yang serba dibatasi dalam rangka menekan persebaran virus Covid-19. Tujuan: Penerapan Family Psycoeducation pada keluarga berdasarkan standar asuhan keperawatan jiwa dilakukan secara online pada klien untuk mengurangi tingkat kecemasan pada keluarga yang memiliki anggota keluarga dengan Covid-19. Metode: Laporan kasus ini menggunakan penerapan Family Psychoeducation dan standar asuhan keperawatan pada klien Covid-19 yang mengalami anxietas. Laporan kasus ini berdasarkan pengalaman praktik klinik peminatan keperawatan jiwa yangtelah dilakukan secara online dimasa pandemi Covid-19. Hasil: Evaluasi telah didapatkan adanya penurunan tingkat kecemasan pada klien dan keluarga yang terkonfirmasi positif Covid-19 yang dilakukan secara online. Terapis juga telah memberikan pre dan post test kuesioner SRQ dimana nilai skor klien berjumlah 8 dan SRQ pada keluarga berjumlah 10. Dalam hal ini pentingnya intervensi dilakukan dalam rangka mengurangi tingkat kecemasan yang terjadi pada klien dan keluarga. Setelah sebulan proses perawatan, hasil skor SRQ klien dan keluarga berada ≤ 6 yang berarti adanya penurunan stress yang dirasakan oleh klien dan keluarga selama dalam perawatan klien di rumah sakit.Kesimpulan: Penerapan Family Psycoeducation pada keluarga berdasarkan standar asuhan keperawatan jiwa dilakukan secara online pada klien dan keluarga untuk mengurangi tingkat kecemasan pada keluarga yang anggota keluarganya terkonfirmasiCovid-19. Evaluasi yang didapatkan adanya penurunan tingkat kecemasan pada klien dan keluarga yang terkonfirmasi positif Covid-19 yang dilakukan secara online.Kata kunci: kecemasan; covid-19; psikoedukasi keluarga